Evaluasi Pelaksanaan Trias Usaha Kesehatan Sekolah (UKS) di Sekolah Dasar Negeri Lawe Kongker Kabupaten Aceh Tenggara Tahun 2021 - Afrizal; Anisa Sukma Ningsih (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
School Health Efforts as education and health efforts must be carried out in an integrated, planned, directed and responsible manner in instilling, growing, developing and guiding to live, enjoy and implement the principles of healthy living in the daily lives of students. The purpose of the study was to determine the organization, implementation of work programs, Availability of facilities and infrastructure Availability of funding sources in the implementation of the School Health Business Trias (UKS) at the Lawe Kongker State Elementary School, Southeast Aceh Regency in 2021. This type of research is descriptive with quantitative analysis. The results of the research on the implementation of the Triassic School Health Business at the Lawe Kongker State Elementary School, Southeast Aceh Regency in good categories, both from the implementation of education, health counseling, and the implementation of a healthy school life environment. Southeast is supported and coordinated by the implementation of the school health business organizational mechanism and the implementation of the school health business work program, both from the school and from the supervisory team of school health business supervisors. Meanwhile, the inhibiting factors for the implementation of School Health Efforts are still low participation or support from parents and the community for School Health Business activities and the lack of availability of funds from parents and the community for School Health Business activities.